When will consumers be ready? A psychological perspective on consumer engagement in social media brand communities. Issue 4 (5th August 2019) - Liu, Linlin; Liu, Renjing; Lee, Matthew; Chen, Jiawen
Abstract : Purpose: The purpose of this paper is twofold: first, to explain whether consumer engagement in social media brand communities (SMBCs) motivates consumer brand loyalty; and second, to explore the antecedents of consumer engagement by developing a model based on personal engagement theory. Design/methodology/approach: Online survey data from 279 brand community members of Weibo (one of the most popular social media websites in China) were used to test the proposed model. Structural equation modeling with partial least squares was performed to test both the measurement model and the structural model. A hierarchical multiple regression analysis was conducted to examine the interaction effects. Findings: The findings show that three factors, namely, recognition, community identification and self-efficacy, had significant positive effects on consumer engagement in SMBCs, which consequently enhanced brand loyalty. Self-efficacy moderated the effects of both community identification and recognition on consumer engagement. The impacts of three factors on consumer engagement are contingent upon the type of SMBCs. Originality/value: This study extends and advances the literature on consumer engagement by explaining consumer engagement in SMBCs from a new theoretical lens. This study also enriches personal engagement theory by investigating the effects of the interaction between different conditions of engagement. In addition, this study contributes to brand loyalty literature by providing empirical evidence of the impact of consumer engagement on brand loyalty. Finally, this study contributes to the online brand community study by introducing personal engagement theory into SMBC context, and examining the moderating role of SMBC types.